(untitled) (European Journal of Health Research, 2023)
Breast cancer is the most frequently diagnosed malignancy in women. Tamoxifen is the adjuvant drug of choice in the endocrine treatment of estrogen receptor-positive breast cancer. It has effects that are very useful with respect to the vaginal epithelium and bone, in addition, it is cardioprotective. On the other hand, it should be noted that after the diagnosis of the disease, there are notable physical and psychological changes that have a great impact on the patient and that, in many cases, is linked to the appearance of depression. The aim of this work was to analyze the evidence regarding the possible interactions between tamoxifen and different antidepressants, as well as their adverse effects in breast cancer patients receiving tamoxifen treatment. For this, a systematic review of the articles published in the last 10 years in the Science Direct, Dialnet, Scielo, Medigraphic and PubMed databases was carried out. After the final selection of 12 documents, the results indicate that the choice of antidepressant in the case of women with breast cancer undergoing treatment with tamoxifen should be made based on the profile, side effects, and possible drug interaction potential. It is essential to pay special attention to the importance of the interactions that can occur between tamoxifen and antidepressants, since this interaction can have an impact on the prognosis of breast cancer and the indication of antidepressants arises from non-oncology specialists. In short, it is essential to take into account that there is no clinical evidence that supports prescribing one antidepressant instead of another with respect to their efficacy and safety, therefore attention must be paid to the different interactions that may arise.